2021
DOI: 10.5535/arm.20127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aqua Therapy Exercises on Postmastectomy Lymphedema: A Prospective Randomized Controlled Trial

Abstract: Objective To investigate the effect of aqua therapy resistance exercise on arm volume, pain, and shoulder range of movements in post-mastectomy lymphedema.Methods This was a single-blind randomized controlled trial. Fifty eligible breast cancer survivors (median, 10 years after surgery) with lymphedema (median, 21% inter-limb difference) were assigned randomly to group A (n=25) or control group B (n=25). The study group underwent 60 minutes of aqua therapy exercise comprising of warm-up for 10 minutes, 40 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…From 4171 records first identified, 3566 titles and abstracts and 504 full texts screened, there were 132 publications from 121 studies included in the final review. Studies included 102 RCTs [ 1 , 2 , 4 , 6 12 , 15 , 16 , 18 , 19 , 21 24 , 26 , 29 32 , 35 , 37 , 38 , 40 , 41 , 45 52 , 55 , 57 , 61 63 , 65 , 67 72 , 75 – 81 , 83 , 84 , 86 88 , 91 99 , 101 , 103 106 , 109 , 110 , 112 – 114 , 116 , 118 – 122 , 124 127 , 129 , 130 , 132 , 133 , 136 – 140 , 143 , 145 , 146 , 149 151 , 153 – 157 ], six randomised RXTs [ 17 , 34 , 36 , 39 , 142 , 152 ], and 13 ob...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From 4171 records first identified, 3566 titles and abstracts and 504 full texts screened, there were 132 publications from 121 studies included in the final review. Studies included 102 RCTs [ 1 , 2 , 4 , 6 12 , 15 , 16 , 18 , 19 , 21 24 , 26 , 29 32 , 35 , 37 , 38 , 40 , 41 , 45 52 , 55 , 57 , 61 63 , 65 , 67 72 , 75 – 81 , 83 , 84 , 86 88 , 91 99 , 101 , 103 106 , 109 , 110 , 112 – 114 , 116 , 118 – 122 , 124 127 , 129 , 130 , 132 , 133 , 136 – 140 , 143 , 145 , 146 , 149 151 , 153 – 157 ], six randomised RXTs [ 17 , 34 , 36 , 39 , 142 , 152 ], and 13 ob...…”
Section: Resultsmentioning
confidence: 99%
“…Some studies showed no difference in effect for type [ 80 , 88 , 106 , 152 , 153 , 156 ], while others showed larger effects of aerobic exercise compared to resistance [ 40 , 63 , 129 ], or for resistance and high intensity interval training compared to aerobic exercise combined with high intensity interval training [ 19 , 113 ]. In other studies, aquatic exercises may have been more effective than land exercises [ 4 ], and Pilates more effective than circuit exercises [ 11 ].…”
Section: Risk Of Biasmentioning
confidence: 99%
“…In addition, studies have shown that aquatic physical therapy not only reduces the lymphedema risk in those with breast cancer [ 17 ], but also relieves persistent skin dryness caused by cancer treatment and significantly decreases the incidence of skin induration, thereby potentially decreasing chances of cancer recurrence [ 18 ]. Meanwhile, it provides a safe, effective and non-invasive method for the treatment of breast cancer survivors, and avoids invasive methods and oral medications that cannot be tolerated over a long period due to their adverse systemic effects [ 19 ]. In light of this, aquatic physical therapy would be an ideal form of physical rehabilitation for patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%